ANALISA DAN PENGENDALIAN RESIKO K3 PADA PROYEK PEMBANGUNAN GEDUNG RUMAH SAKIT ADVENT KOTA PALANGKA RAYA ( Ohs Risk Analysis And ControlIn Palangka Raya City Advent Hospital Building Project ) - Maretina Eka Sinta; Marselinus Jelalu (Huma Tabalien Jurnal (HTJ) Teknik Sipil, 2022)
Palangka Raya, which is a big city, does not rule out the possibility of always building facilities and infrastructure, such as the construction of the Palangka Raya City Adventist Hospital building. The implementation of OSH in construction projects plays an important role in maintaining, protecting and creating a safe, healthy and accident-free environment. In the implementation of the K3 program several related parties must always provide direction for construction workers, but besides that the level of understanding and knowledge of the workers who are very minimal can cause obstacles in implementing the K3 program. This study aims to determine the implementation of the K3 program and the obstacles in implementing it in the construction project of the Adventist Hospital Building in Palangka Raya City. This research was conducted by distributing questionnaires on construction projects in Palangka Raya. With the results of distributing questionnaires in 1 construction project with a total of 6 respondents who have a role. And their respective tasks in the construction project. Data analysis was carried out at the project field location, followed by data processing using the respondent's method to determine field data. Based on the results of the analysis, it is known that the K3 program field respondents concluded that protecting the public by installing K3 signs inside and outside the project as well as marking the presence of heavy vehicle lanes is very important to always remind workers about the importance of work safety and urge the public to always be careful while on the road. near an ongoing construction project. As for the obstacles in implementing OSH, the field values obtained conclude that the obstacles in implementing OSH are on the workers' side, this occurs due to the lack of knowledge of workers about OSH and the demands of workers who are still on basic needs by not prioritizing their own safety. Keywords : occupational safety and health, K3, K3 programs, obstacles to implementing K3